Transformasi Kelembagaan Pendidikan Islam di Andalusia: Dari Sistem Madrasah ke Model Universitas: - - Ulya Afif, Yusmicha; Ratna Etikasari Agus (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study examines the transformation of Islamic education in Andalusia from the madrasah system to university-like institutions, with particular attention to institutional structures, curricula, and academic practices. The research focuses on how Andalusian madrasahs developed formal educational features such as structured curricula, multidisciplinary knowledge integration, teacher authorization systems (ijāzah), and academic autonomy, which later influenced the formation of medieval European universities. This study employs a qualitative historical research method based on literature analysis. Primary sources include classical Andalusian texts and works of prominent scholars such as Ibn Rushd, Ibn Bājjah, and Ibn Ṭufayl, while secondary sources consist of contemporary historical and educational studies. Data analysis was conducted through three stages: (1) historical-descriptive analysis to reconstruct the development of educational institutions and curricula in Andalusia; (2) interpretative analysis to examine the role of madrasahs in shaping academic authority, teaching methods, and knowledge transmission; and (3) comparative analysis to identify similarities between Andalusian madrasahs and early European universities. The findings indicate that Islamic education in Andalusia experienced a significant institutional transformation, characterized by the emergence of madrasahs with organized curricula encompassing religious sciences, philosophy, medicine, mathematics, and astronomy, supported by extensive libraries and an inclusive academic environment. These institutions also implemented systems of scholarly certification and academic autonomy that closely resemble the foundational structures of medieval European universities. This study highlights the substantial contribution of Islamic educational institutions in Andalusia to the historical development of higher education and underscores the need for a more inclusive global historiography of education